P08.18 Regional variation in emergency department presentation rates of chlamydia related morbidity in four states of australia. (13th September 2015) - Goller, JL; De Livera, AM; Guy, RJ; Fairley, CK; Hocking, JS
Abstract : Background: Pelvic inflammatory disease (PID) and ectopic pregnancy among women and epididymitis among men are important sequelae of chlamydia. In Australia, chlamydia prevalence is higher among younger populations, Indigenous Australians, and in regional and remote areas. The burden of chlamydia sequelae by Australian region is unknown. We assessed if rates of emergency department (ED) presentations in Australia for chlamydia sequelae vary by remoteness of residence. Methods: Age and sex specific ED rates per 100, 000 population of PID, ectopic pregnancy or epididymitis among 15–44 year-old Victorian, New South Wales, Queensland and South Australian residents were calculated for the years 2009 and 2010 using hospital and Australian Bureau of Statistics estimated resident population data. Logistic regression was used to assess regional variation in rates and adjusted for age, remoteness and socio-economic group (SES) of residential postcode in deciles. Results: During 2009–2010, overall ED rates per 100, 000 among 15–44 year-old residents from all four states were 76.8 (95% CI: 74.8–78.8) for PID, 73.0 (95% CI: 71.1–75.0) for ectopic pregnancy and 86.4 (95% CI: 84.3–88.4) for epididymitis. Multivariable analysis showed that PID rates in female residents: were higher in inner-regional (AOR = 1.6; 95% CI: 1.5–1.7) and outer regional/remote areas (AOR = 2.1; 95% CI: 1.9–2.3) compared with metropolitan areas; increased by 6%(95% CI: 5%–7%) per decile of increasing disadvantage of postcode; and were higher in women aged 15–24 (AOR = 2.4, 95% CI: 2.3–2.6) and 25–34 years (AOR = 1.7; 95% CI: 1.6–1.8) compared with 35–45 years. Ectopic pregnancy rates in females were higher in inner-regional (AOR = 1.3; 95% CI: 1.2–1.4) and outer regional/remote (AOR = 1.7; 95% CI: 1.5–1.8) areas; increased by 6% (95% CI: 5%–7%) per decile of increasing disadvantage; and were highest among 25–34 year-old women (AOR: 2.1; 95% CI: 2.0–2.3). In men, epididymitis rates were higher in inner-regional (AOR = 1.6; 95% CI: 1.5–1.7) and outer regional/remote (AOR = 2.3; 95% CI: 2.2–2.5) areas and did not differ by age or SES. Conclusion: Possible explanations for higher ED rates of chlamydia sequelae in non-metropolitan Australian residents could be higher chlamydia prevalence or variable access to primary healthcare in these areas. Disclosure of interest statement: These data are being analysed as part of the Australian Chlamydia Control Effectiveness Pilot (ACCEPt) study funded by the Commonwealth Department of Health and the National Health and Medical Research Council.